ANALISIS FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Andafiya, Robiatul; Ediyanto, Ediyanto; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2024)
This research uses quantitative research methods. The populations in this research are companies registered in Property and Real Estate with a sample of 11 companies. The results of hypothesis testing regarding the direct impact of using Smart PLS 3.0, show that company size is positivelty significant to profitability, capital structure is negativelty significant to profitability, liquidity is negatively but not significant to profitability, compony size is positively but not significant to compony value, structure capital is negative but not significant to company value, Likuidity is negatively significant to company value, Profitability is positive but not significant to company value. The result of the indirect influence hypothesis test show that the Company Size variable is positive but not significant on company value through Profitability, Capital Sructure is negative but not significant on company value through Profitability, Liquidty is negative but not significant company value throught Profitability.